2021
DOI: 10.1002/solr.202100238
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Solvent Additives for the Fabrication of Polymer:Fullerene Solar Cells: Exploring a Series of Benzaldehydes

Abstract: The power conversion efficiencies of organic solar cells delicately depend on the morphology of the light‐harvesting bulk heterojunctions (BHJ). Upon deposition from solution, the formation of tailored bicontinuous networks of polymers and fullerenes is often achieved using combinations of solvents and solvent additives. Common wisdom infers that best solar cell performances are achieved when the solvent additives exhibit excellent fullerene solubility. Herein, this concept is revisited based on the investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…We will demonstrate in the following that selective Cu infiltration can be applied as a convenient staining method to analyze the size and interconnectivity of PTB7 and PC 71 BM domains in BHJ layers. For this purpose, we analyzed different PTB7:PC 71 BM layers with nanomorphologies that were tuned by using different processing additives (AA, SA, and DIO) during layer deposition . It will be shown that Cu staining can be exploited not only for STEM imaging but also for SE-SEM imaging as a prerequisite for the 3D reconstruction of the BHJ domain structure by FIB-SEM tomography.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We will demonstrate in the following that selective Cu infiltration can be applied as a convenient staining method to analyze the size and interconnectivity of PTB7 and PC 71 BM domains in BHJ layers. For this purpose, we analyzed different PTB7:PC 71 BM layers with nanomorphologies that were tuned by using different processing additives (AA, SA, and DIO) during layer deposition . It will be shown that Cu staining can be exploited not only for STEM imaging but also for SE-SEM imaging as a prerequisite for the 3D reconstruction of the BHJ domain structure by FIB-SEM tomography.…”
Section: Resultsmentioning
confidence: 99%
“…Only upon using DIO, an additional drying step was applied at an elevated temperature (50 °C, 20 min) on the next day to remove DIO residues. More details on the absorber-layer fabrication are described in the literature …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[18,19] Additive strategy, thermal annealing, and solvent annealing are common methods to modulate the morphology of BHJ OSCs, but the introduction of the former is often accompanied by a decrease in device stability, and the post-treatment means exacerbate the complexity of production preparation, which is not conducive to the future commercial production. [20][21][22][23][24][25][26] In contrast to BHJ OSCs, the layer-by-layer solution spin-coating method, also known as the two-step method, allows for separate regulation of the donor and acceptor layer to form the desired vertical structure, which facilitates charge transport and collection, does not rely on the ratio of the donor to acceptor, and is less dependent on the use of additives, solvent concentration, etc. [27][28][29] It is a promising production method to prepare high-efficiency devices.…”
Section: Introductionmentioning
confidence: 99%